a) a² + 81
б) -10x + 1
в) 12x - 9
г) a² + 4ab
Объяснение:
Формула квадрата разности: (a - b)² = a² - 2ab + b²
Формула квадрата суммы (a + b)² = a² + 2ab + b²
а) 18a + (a - 9)² = 18a + a² - 2 * 9*a + 9² = 18a + a²- 18a + 81 = a² + 81
б) (5x - 1)² - 25x² = (5x)² - 2 * 5x*1 + 1² - 25x² = 25x² - 10x + 1 - 25x² = -10x + 1
в) 4x² - (2x - 3)² = 4x² - ((2x)² - 2 * 2x*3 + 3²) = 4x² - (4x² - 12x + 9) = 4x² - 4x² + 12x - 9 = 12x - 9
г) (a + 2b)² - 4b² = a² + 2 * a*2b + (2b)² - 4b² = a² + 4ab + 4b² - 4b² = a² + 4ab
ответ:
d=b^2-4ac=(-1)^2-4*1*(-72)=1+288=\sqrt{289}
289
=17
х1=\frac{-b- \sqrt{d} }{2a} = \frac{1-17}{2} = \frac{-16}{2} =-8
2a
−b−
d
=
2
1−17
=
2
−16
=−8
х2=\frac{-b+ \sqrt{d} }{2a} = \frac{1+17}{2} = \frac{18}{2} = 9
2a
−b+
d
=
2
1+17
=
2
18
=9
ответ: -8 и 9
d=b^2-4ac=7^2-4*(-4)*(-3)=49-48=\sqrt{1} =1
1
=1
х1=\frac{-b- \sqrt{d} }{2a} = \frac{-7-1}{2*(-4)} = \frac{-8}{-8} =1
2a
−b−
d
=
2∗(−4)
−7−1
=
−8
−8
=1
х2=\frac{-b+ \sqrt{d} }{2a} = \frac{-7+1}{(-8)} = \frac{-6}{-8} =0,75
2a
−b+
d
=
(−8)
−7+1
=
−8
−6
=0,75
если неверно, извини